Rheology : concepts, methods, and applications - Malkin, A. I︠A︡; Isayev, Avraam I., 1942- (ChemTec Publishing, 2022)
"The fourth edition of this excellent book, used by many universities and companies for teaching and research purposes, brings significant current information on new methods and applications based on recently published literature. The most notable new sections discuss non-Newtonian properties and their effect on material processing, heterogeneity in flow, rheology of highly concentrated emulsions and suspensions, viscosity and viscoelastic behavior of nanocomposites, the behavior of supramolecular solutions, rheology of gels, deformation-induced anisotropy, conformation changes during flow, and molecular orientation."-- Provided by publisher
Keywords: Rheology -- Textbooks.; elektronické knihy; electronic books